Establishment and evaluation of real-time PCR based SELEX platform for the identification of protein binding aptamers: A pilot study in Sri Lanka - Abeykoon, A.I.; Kumarasinghe, K.M.N.; Chandrasekharan, N.V.; Wickramasinghe, P.M.T.B. (National Science Foundation: Colombo, 2025)
Aptamers are single-stranded DNA (ssDNA) affinity reagents capable of substituting conventional antibodies in processes of molecular recognition. Their higher affinities, lower costs of production and longer shelf lives of aptamers are making them increasingly popular and replacing conventional antibodies in the fields of diagnostics and therapeutics. Systematic evolution of ligands by exponential enrichment (SELEX) is a well-established and efficient technology for generation of aptamers with high affinity against various targets including whole cells, isolated proteins, and small molecules. This study is the first to report efforts in exploring SELEX for isolating protein-binding aptamers using a quantitative PCR and NGS-based approach in a local context. A low-cost selection platform was developed by coating microwell plates with human serum albumin, the target protein of interest, for quantitative and qualitative solid phase immunoassays. Changes in affinity and diversity were monitored through analysis of amplification plots, melt curves, remelt curves and high-resolution melt curve (HRM). Following eight selection cycles, the enriched DNA was subjected to high-throughput sequencing, and the two most abundant sequences were identified. The sequences were evaluated through in-silico binding assays, which resulted in comparable binding affinities expected for aptamers. Among the monitoring techniques, the amplification curve analysis was a valuable tool in understanding changes in pool affinity. Although the melt curve initially lacked sufficient resolution in the early stages of SELEX, the re-melt curve and HRM analysis accurately reflected pool diversity during this time. Thus, we demonstrate that it is feasible to use locally available technology for the successful development of aptamers. This highlights the potential to produce affinity reagents locally on a commercial scale in the future.
Keywords: PCR; Protein bindiny aptamers; SELEX platform